Study of Zircon Crystals: An Implication to Determine of Source and Temperature of Crystallization in Turkeh Dareh Pluton, NW Iran - M. Jamshidibadr (Journal of Sciences, Islamic Republic of Iran)
Turkeh Dareh pluton is outcrop in NW of Iran and it is one of the intrusions in Sanandaj-Sirjan zone. Shaped crystals of this pluton distinct oscillatory zoning narrow and close together zoning in zircons indicate parental magma richness of zirconium. Factors affecting the shape of the zircon crystals are the composition, possibly the temperature of the crystallization, water content in magma and origin of the magma, therefore, were studied morphology of zircon crystals of Turkeh Dareh pluton. Morphologically, most of Turkeh Dareh zircons are located in range of S13 and S14 and in lesser extent in the range of S18, S19 and S20. The minimum zircons crystallization temperature was calculated 750 to 840 Cº based on the morphology of zircon, zircon saturation and the whole rock geochemistry. The origin of intrusion magma of Turkeh Dareh is I-type and calc-alkaline that these results are consistent with results of field observations, mineralogy and geochemistry of this pluton.